Research on Calibration Method of Infrared Temperature Measurement System Near Room Temperature Field - Cui, Shuanglong; Xing, Jian (Frontiers in Physics, 2022)
The calibration accuracy of the infrared temperature measurement system near room temperature field is easily affected by the calibration environment. In this paper, an equivalent blackbody calibration method is proposed for this problem. In this method, the target radiation and ambient radiation superimposed in calibration data are separated by two calibration functions at different ambient temperatures, and an equivalent blackbody calibration function is constructed. The experimental verification of the proposed method is carried out, and the results show that the proposed method has a better calibration effect for the surface blackbody than the commonly used environmental compensation methods. This method can effectively improve the calibration accuracy of infrared temperature measurement system near room temperature field, and further improve the infrared temperature measurement theory.